GAMBARAN GANGGUAN KOGNITIF DAN FUNGSIONAL (IADL)PADALANSIA DI KELURAHAN KRAMAS,KECAMATAN TEMBALANG, KOTA SEMARANG - Insani Kamilia Tanjung; Ari Udiyono; Nissa Kusariana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Individuals at the age of 65 are at high risk of suffering dementia. Dementia is the primary cause of disability and limitation in elderly. In addition, the cost of caring for family members who suffer from dementia can bring a striking impact on the sustainability of households. In less than four years, at least 10% of the Indonesian population is of age 60 years and older. Hence, making dementia one of the must-watch diseases in Indonesia. This research aimed to calculate the prevalence and describe the characteristics of suspected dementia elderly in Kramas Village, Tembalang District, Semarang City. This was a descriptive observational research with a cross sectional approach. The total population were 114 elderly of 60-74 years old which all subjects were taken to be measured. The measurement of cognitive impairment was examined using the Mini Mental State Examination (MMSE) questionnaireand the disability to perform executive functions was inspected using the Lawton Instrumental Activities of Daily Living (Lawton IADL) questionnaire.Cognitive impairment was found in both sexes: female (46.8%) and male (45.5%), and mostly occured in age 65-74 years old (51.1%), low level of completing elementary school (65.0%), and living in Rukun Warga (RW) 3 area (53.3 %). Most respondents were able to perfom IADL (59.2%) autonomously.